PENGEMBANGAN GAME EDUCATION DENGAN MATERI PENGENALAN PENJUMLAHAN SEDERHANA UNTUK SEKOLAH DASAR MENGGUNAKAN APLIKASI CONSTRUCT 2 - M, Maemunah; Mas'ud, Huzaima (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2024)
Education is undergoing significant transformation in the ever-evolving digital era. Educators are increasingly required to integrate technology into learning to create more dynamic and engaging experiences for students. Interest in mathematics often diminishes when students encounter concepts that are perceived as difficult and abstract. Therefore, a learning approach that enhances students' understanding and skills is necessary. This research aims to design and develop educational games using the Construct application as an innovative step towards advancing mathematics learning for elementary school students. The Research and Development (R&D) method was employed, utilizing the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) approach. This structured and systematic approach enables researchers to design, develop, and evaluate educational programs more effectively. The development process in this study has led to significant advancements in mathematics education at the elementary school level through an innovative approach using the Construct application. The results reveal several key findings that demonstrate the relevance and impact of the developed educational game program. The Construct application has proven to be a powerful platform for creating interactive and engaging educational games, allowing educators to design captivating learning experiences for students.